Women Adapting : Bringing Three Serials of the Roaring Twenties to Stage and Screen - Wood, Bethany, 1975- (Book collections on Project MUSE., 2019)
"In Women Adapting, Bethany Wood examines how the developing preference for adaptations in early twentieth century entertainment promoted interrelationships among fiction, theatre, and film. Weaving together a broad range of archival sources, including personal correspondence, rejected rough drafts, advertisements, films, periodical illustrations, contracts, 'lost' songs, and film stills, Wood deftly explores how early-twentieth-century processes of adaptation forged connections across industries in entertainment. By centering her cross-disciplinary study on issues of gender, Wood considers how inter-industrial systems of adaptation affect both women writers and the female characters they create"--